(3GdebGdjO GdhLhOjIs - (3YHO GdMb Hf EHQGgje Hf eMeO Hf fUQ GHf SHYjf GdETHjdj GdeQSj GdnqQbhWj, bWH GdOjf CHh eMeO,J (B669 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMehO GdPGJ , GdeYXe ef cd GdLgGJ GdeTGQ Edjg HGdUdhGJ hGdJMjGJ s
(3BNQgG (B:s
(3BNQg eHJhQ jfJgi CKfGA GdcdGe ai aUd YfhGfg (B: ( (3afHOC HcdGe GdebQH ceG hYO afbhd (B) (3hBNQ eG ajg (B: (3hdG jecf Pdc ajgG , dGWHYkG hdG YQVkG , hGddg jNdUfG ef JHGd GdMQeGf hGddg bOLYd GdCSHGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B280 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B90s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJUha hGdBOGH GdTQYjIs